2009
DOI: 10.4049/jimmunol.0901099
|View full text |Cite
|
Sign up to set email alerts
|

The p110δ Isoform of Phosphatidylinositol 3-Kinase Controls Susceptibility to Leishmania major by Regulating Expansion and Tissue Homing of Regulatory T Cells

Abstract: Resistance to Leishmania major and most intracellular pathogens is usually associated with a strong T cell-mediated immunity, particularly a CD4(+) Th1 response. Mice with an inactivating knock-in mutation in the p110delta isoform of PI3K (referred to as p110delta(D910A)) show severely impaired T cell responses. Because a strong T cell response is thought to mediate resistance to intracellular pathogens, we examined the outcome of L. major infection in p110delta(D910A) mice. Paradoxically, p110delta(D910A) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
104
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(114 citation statements)
references
References 62 publications
7
104
1
Order By: Relevance
“…A recent study by Liu et al (27) has found that PI3Kδ also controls susceptibility to CL caused by L. major by regulating the expansion and tissue homing of the Tregs that are involved in pathogenesis (27). In the present study, we found that although PI3Kγ blockade/deficiency significantly reduced recruitment of Tregs to the lesion, it had no effect on development, expansion, or IL-10 production from these cells.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…A recent study by Liu et al (27) has found that PI3Kδ also controls susceptibility to CL caused by L. major by regulating the expansion and tissue homing of the Tregs that are involved in pathogenesis (27). In the present study, we found that although PI3Kγ blockade/deficiency significantly reduced recruitment of Tregs to the lesion, it had no effect on development, expansion, or IL-10 production from these cells.…”
Section: Discussioncontrasting
confidence: 44%
“…In the present study, we found that although PI3Kγ blockade/deficiency significantly reduced recruitment of Tregs to the lesion, it had no effect on development, expansion, or IL-10 production from these cells. Interestingly, Liu et al (27) found that PI3Kδ was not involved in mediating uptake of parasites into host phagocytes. This is perhaps not surprising, because both PI3Kγ and PI3Kδ, which are primarily expressed in hematopoietic cells and endothelial cells, have been reported to have related yet nonredundant roles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L-glutamine, 100 U/mL penicillin, and 100 μg/mL streptomycin (Invitrogen Life Technologies, Burlington, Ontario, Canada). For infection, mice were injected in the right hind footpad with 5 × 10 6 stationary phase promastigotes in 50 μL PBS as previously described [38]. Lesion sizes were monitored weekly by measuring footpad swellings with calipers.…”
Section: Micementioning
confidence: 99%
“…Six to 8 weeks old homozygous PIP KO mice (backcrossed >9 generations into CD1 background) and WT CD1 mice were obtained from our in-house breeding colony managed by the Central Animal Care Services, University of Manitoba. All animal experiments were approved by the University of Manitoba stationary phase promastigotes in 50 μL PBS as previously described [38]. Lesion sizes were monitored weekly by measuring footpad swellings with calipers.…”
Section: Micementioning
confidence: 99%